The effects of high-repetition strength training on performance in competitive endurance athletes: a systematic review and meta-analysis - Nugent, F. J.; Flanagan, E. P.; Darragh, I.; Daly, L.; Warrington, G. D. (The Journal of Strength and Conditioning Research, 2023)
The aim of this systematic review and meta-analysis was to evaluate the effects of high-repetition strength training (HRST) on performance in competitive endurance athletes. The methodology followed the Preferred Reporting Items for Systematic Review and Meta-Analysis protocol. A search of databases was performed until December 2020. Inclusion criteria were (a) competitive endurance athletes, (b) =4 weeks HRST intervention, (c) control or comparison group, (d) outcome measures of performance (either physiological or time trial performance), and (e) all experimental designs. Quality assessment was performed using the Physiotherapy Evidence Database (PEDro) scale. Of the 615 studies retrieved, 11 studies were included (216 subjects) and 9 studies provided sufficient data for the meta-analysis (137 subjects). The PEDro scale score had a mean of 5 of 10 points (range: 3-6). There was no significant difference between the HRST and control groups (g = 0.35; 95% confidence interval [CI] = -0.38 to 1.07; p = 0.35) or HRST and low-repetition strength training (LRST) groups (g = 0.24; 95% CI = -0.24 to 0.72; p = 0.33). The findings of this review and meta-analysis indicate that HRST does not result in improved performance over a 4- to 12-week period, and the results seem to be similar to LRST. The majority of studies involved recreational endurance athletes and had a mean duration of 8 weeks, which is a limitation of the findings. Future intervention studies should be > 12 weeks in duration and involve well-trained endurance athletes (maximal oxygen uptake [Vo2max] of >65 ml·kg-1·min-2).